Delinquency Among Members of Hong Kong Youth Street Gangs: The Role of the Organizational Structures of Gangs and Triad Affiliations - Chui, Wing Hong (International journal of offender therapy and comparative criminology, 2018)
This study explores the importance of organizational structures and formal affiliations with the Hong Kong triads to delinquency among youth street gang members in Hong Kong. More specifically, this study examines the relative importance of the number of organizational structures and triad affiliation to patterns of delinquency in a sample of active members of youth street gangs (N = 201). With the aid of outreach social workers, a convenience sampling method was used to recruit a gender-balanced sample of at-risk youths. Logistic regression analysis of the survey data that was gathered indicated that formal affiliation to Hong Kong triads and the presence of organizational structures significantly increased the odds of delinquency (independently of each other). Suggestions for future research on gang membership and delinquency, with particular reference to the Asian context, are provided.